Duration of Hospital Stay Following Orthognathic Surgery at the Jordan University Hospital - Jarab, Fadi (Springer-Verlag, 2011)
BACKGROUND: Major oral and maxillofacial surgery procedures have been routinely performed on an inpatient basis in order to manage both, the recovery from anesthesia and any unpredictable morbidity that may be associated with the surgery. The use of inpatient beds is extremely expensive and if the surgical procedures could be done on an outpatient setting, it would reduce the costs and the need for inpatient care. The aim was to determine the length of hospital stay (LHS) and the factors which influence the LHS following orthognathic surgery at the Jordan University Hospital over 5 years (2005–2009). METHODS: This was a retrospective record review of patients who underwent orthognathic surgery at Jordan University Hospital between 2005 and 2009. The variables were recorded on a data capture form which was adapted and developed from previous studies. Descriptive and analytical statistical methods were used to correlate these variables to the LHS. RESULTS: Ninety two patients were included in the study and 74% of them were females. The mean age was 23.7 years and the mean LHS was 4 days. The complexity of the procedure, length of operation time, intensive care unit (ICU) stay and year of operation were significantly correlated with a positive LHS (P < 0.05). CONCLUSION: Patients’ hospital stay was directly related to the complexity of the orthognathic procedure, the operation time, time spent in ICU and the year in which the operation was done. There was a significant reduction in the LHS over the progressing years and this could be due to an increase in experience and knowledge of the operators and an improvement in the hospital facilities.